MANAGEMENT: MUCH MORE INTERDISCIPLINARY THAN YOU THINK - Anstine, Jeffrey (European Scientific Journal, ESJ, 2015)
The discipline of Management is typically associated with schools of business and is thought to be a professional or pre-professional degree. Hence, it is commonly separated from the Liberal Arts and any discussions about interdisciplinary topics. However, the roots of management are in Economics, Psychology and other disciplines with ties across many different subjects. In this paper I go through management textbooks and read the primary sources used for the content covered in various chapters. A significant amount of the citations for the material is from academic journals in Psychology, great works by Philosophers, classic writings by Economists and other areas in the Social Sciences. This paper illustrates the interdisciplinary nature of a subject that is not traditionally thought to be one.